20th Psychology Days in Zadar: Book of Selected Proceedings - ompadmin; Burić, Irena (2019)
Psychology Days in Zadar is an international conference organized biennially by the Department of Psychology of the University of Zadar. It started over 40 years ago and has evolved over decades into a recognizable psychology conference that attracts many researchers from Croatia and abroad. Participants to the conference may enjoy high quality dissemination of scientific and professional knowledge from all psychology fields, as well as the pleasant and warm Mediterranean surroundings of the city of Zadar along with its beautiful nature and distinct culture.The 20th jubilee Psychology Days conference in Zadar was held on May 19-21 2016. It was organized by an international organizational-scientific committee and gathered over 400 participants from Croatia, Austria, Belgium, Bosnia and Herzegovina, Ireland, Serbia, Slovenia, Sweden, US, and UK who presented their work through three invited lectures, three symposia, thirteen oral sessions, two poster sessions, four workshops, two round tables and three student sessions. The number of participants, as well as the amount of good quality research papers which were presented at the conference, encouraged us to engage in a demanding but rewarding process of collecting the most interesting research to be published in the Book of Selected Proceedings of 20th Psychology Days in Zadar.